Are there any general formula for the following series

$$\tag{1}\sum_{n\geq 1}\frac{H^{(p)}_nH_n}{n^q}$$

Where we define

$$H^{(p)}_n= \sum_{k=1}^n \frac{1}{k^p}\,\,\,\,\,H^{(1)}_n\equiv H_n =\sum_{k=1}^n\frac{1}{k} $$

For the special case $p=q=2$ in (1) I found the following paper

Stating that

$$\sum_{n\geq 1}\frac{H^{(2)}_nH_n}{n^2}=\zeta(5)+\zeta(2)\zeta(3)$$

See equation (3a) .

Is there any other paper in the literature discussing (1) or any special cases ?


A couple of places to start for further looking:

The paper Further summation formulae related to generalized harmonic numbers by Zheng mentions the $p = q = 2$ case in example 2.3, and has several related results, but not explicitly of the form you're looking for.

Appendix B of the paper On some log-cosine integrals related to $\zeta(3), \zeta(4)$ and $\zeta(6)$ by Mark Coffey has some similar things, and maybe looking through its references and papers that cite it would yield more.

  • $\begingroup$ p.s. I love your site, which I didn't know before, and the challenges you've been running on mymathforum. $\endgroup$ – davidlowryduda Dec 14 '13 at 2:22

Here we provide an answer for $p=1$ and arbitrary $q \ge 2$. Let us denote the quantity in question as follows: \begin{equation} {\mathfrak S}^{(p,1)}_q := \sum\limits_{m=1}^\infty \frac{H^{(p)}_m H_m}{m^q} \end{equation} In order to calculate the above we start from the generating function. We have: \begin{eqnarray} \sum\limits_{m=1}^\infty H^{(p)}_m H_m \frac{t^m}{m} &= & - \int\limits_0^t \frac{\log(1-\xi/t)}{\xi} \cdot \frac{Li_p(\xi)}{1-\xi} d\xi \\ &=& \left\{ \begin{array}{rr} -\frac{1}{3} [\log(1-t)]^3 -\log(1-t) Li_2(t) + Li_3(t) & \mbox{for $p=1$} \\ \cdots \end{array} \right. \end{eqnarray} Now we use the common trick,i.e. we divide by $t$ and multiply by an appropriate power of $\log(1/t)$ and integrate appropriately. We have: \begin{eqnarray} {\mathfrak S}^{(1,1)}_q &=& \underbrace{-\frac{1}{3} \int\limits_0^1 \frac{[\log(1/\xi)]^{q-2}}{(q-2)!} \cdot \frac{[\log(1-\xi)]^3}{\xi} d\xi}_{I_1} +\\ &&\underbrace{\int\limits_0^1 \frac{[\log(1/\xi)]^{q-2}}{(q-2)!} \cdot \frac{Li_1(\xi) Li_2(\xi)}{\xi} d\xi}_{I_2}+\\ &&\underbrace{\int\limits_0^1 \frac{[\log(1/\xi)]^{q-2}}{(q-2)!} \cdot \frac{ Li_3(\xi)}{\xi} d\xi}_{I_3} \end{eqnarray} Clearly all the inthree integrals in here have already been dealt with in MSE. The last integral is trivial . We have: \begin{equation} I_3= Li_{q+2}(+1) \end{equation} The second integral has been evaluated in An integral involving product of poly-logarithms and a power of a logarithm.. We have: \begin{equation} I_2= \frac{1}{2}\left[ \zeta(2) \zeta(q) + \sum\limits_{j=1}^{q-3} j \zeta(q-j-1) \zeta(j+3)-\sum\limits_{j=1}^{q-2} j {\bf H}^{(q-j-1)}_{j+3}(+1) \right] \end{equation} where the quantities highlighted in bold font have been calculated in Calculating alternating Euler sums of odd powers .They all reduce to single zeta values for $q+2\le 7$ and otherwise involve a few additional two-dimensional zeta values. Finally the first integral has been evaluated in Compute an integral containing a product of powers of logarithms. .It always reduces to single zeta values. We have: \begin{eqnarray} &&I_1 = \\ &&\frac{(-1)^{q-1}}{(q-1)!} \left[ -\frac{1}{3} \Psi^{(q+1)}(1) + \frac{1}{2} \sum\limits_{j=1}^{q-2} \binom{q-1}{j} \left\{\Psi^{(j+1)}(1)\Psi^{(q-1-j)}(1) + \Psi^{(j+0)}(1)\Psi^{(q-j)}(1)\right\}+\right.\\ && \left. -\frac{1}{3} \sum\limits_{1 \le j < j_1 \le q-2} \frac{(q-1)!}{j! (j_1-j)!(q-1-j_1)!} \Psi^{(j)}(1) \Psi^{(j_1-j)}(1) \Psi^{(q-1-j_1)}(1) \right] \end{eqnarray} where $\Psi^{(j)}(1)= (-1)^{j+1} j! \zeta(j+1)$ for $j=1,2,3,\cdots$.


You can refer to the following papers

$1$. Evaluations of some quadratic Euler sums

$2$. Euler sums and integrals of polylogarithm functions

$3$. Multiple zeta values and Euler sums

$4$. Tornheim type series and nonlinear Euler sums


In here we provide a generating function of the quantities in question. Let us define: \begin{equation} {\bf H}^{(p,r)}_q(t) := \sum\limits_{m=1}^\infty H_m^{(p)} H_m^{(r)} \frac{t^m}{m^q} \end{equation} In here we take $q\ge1$. We have: \begin{eqnarray} &&{\bf H}^{(p,1)}_q(t) = Li_p(1) \cdot \frac{1}{2} [\log(1-t)]^2 \cdot 1_{q=1}+\\ &&\frac{(-1)^{q}}{2} \sum\limits_{l=(q-2)}^{p+q-3} \left(\binom{l}{q-2} 1_{l < p+q-3} + ({\mathcal A}^{(p)}_{q-2}) 1_{l=p+q-3}\right) \cdot \underbrace{\int\limits_0^1 \frac{[Li_1(t \xi)]^2}{\xi} Li_{l+1}(\xi) \frac{[\log(1/\xi)]^{p+q-3-l}}{(p+q-l-3)!}d\xi}_{I_1}+\\ && \frac{(-1)^{q-1}}{2} \sum\limits_{j=0}^{q-3} \left({\mathcal A}^{(p)}_{q-2-j}\right) \cdot \zeta(p+q-2-j) \underbrace{\int\limits_0^1 \frac{[Li_1(t \xi)]^2}{\xi} \frac{[\log(\xi)]^j}{j!} d\xi}_{I_2}+\\ && \sum\limits_{l=1}^p \underbrace{\int\limits_0^1 \frac{Li_q(t \xi)}{\xi} Li_l(\xi) \frac{[\log(1/\xi)]^{p-l}}{(p-l)!} d\xi}_{I_3} \end{eqnarray} Here $t\in (-1,1)$ and $p=1,2,\cdots$ and \begin{equation} {\mathcal A}^{(p)}_{q} := p+\sum\limits_{j=2}^{q} \binom{p+j-2}{j} = p \cdot 1_{p=1} + \frac{p+q-1}{p-1} \binom{p+q-2}{q}\cdot 1_{p > 1} \end{equation}

Note 1: The quantities in the right hand side all contain products of poly-logarithms and a power of logarithm. Those quantities, in principle, have been already dealt with in An integral involving product of poly-logarithms and a power of a logarithm. for example.

Note 2: Now that we have the generating functions we will find recurrence relations for the sums in question and hopefully provide some closed form expressions .

Now we have: \begin{eqnarray} &&I_1 =\\ &&\sum\limits_{l_1=2}^{l+1} \binom{p+q-2-l_1}{l+1-l_1} (-1)^{l+1-l_1} \zeta(l_1) \left({\bf H}^{(1)}_{p+q-l_1}(t) - Li_{p+q+1-l_1}(t) \right)+\\ &&\sum\limits_{l_1=2}^{p+q-2-l} \binom{p+q-2-l_1}{l} (-1)^{l-1} \zeta(l_1) \left({\bf H}^{(1)}_{p+q-l_1}(t) - Li_{p+q+1-l_1}(t) \right)+\\ &&\sum\limits_{l_1=1}^{p+q-2-l} \binom{p+q-2-l_1}{l} (-1)^{l-0} \left( {\bf H}^{(l_1,1)}_{p+q-l_1}(t) - {\bf H}^{(l_1)}_{p+q+1-l_1}(t) \right) \end{eqnarray} and \begin{eqnarray} &&I_2=2 (-1)^j \left[ {\bf H}^{(1)}_{j+2}(t) - Li_{j+3}(t)\right] \end{eqnarray} and \begin{eqnarray} &&I_3=\\ &&\sum\limits_{l_1=2}^l \binom{p-l_1}{p-l}(-1)^{l-l_1} \zeta(l_1) Li_{p+q+1-l_1}(t) +\\ && \sum\limits_{l_1=2}^{p-l+1} \binom{p-l_1}{l-1}(-1)^{l} \zeta(l_1) Li_{p+q+1-l_1}(t)- \sum\limits_{l_1=1}^{p-l+1} \binom{p-l_1}{l-1} (-1)^l {\bf H}^{(l_1)}_{p+q+1-l_1}(t) \end{eqnarray}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.